Growth and characteristics of AlGaN/GaN heterostructures on sp2-bonded BN by metal–organic chemical vapor deposition. Issue 15 (28th July 2016) - Paduano, Qing; Snure, Michael; Siegel, Gene; Thomson, Darren; Look, David
Abstract: Abstract : AlGaN/GaN heterostructures were grown by metal–organic chemical vapor deposition (MOCVD) on sp 2 -bonded BN using AlN as a nucleation layer. The best x-ray diffraction rocking curve full-width-at-half-maximums (FWHMs) are 0.13° and 0.17° for the GaN (0002) and ( 1012 ) diffraction peaks. Hall-effect measurements show room temperature mobility near 2000 cm/V·s with sheet carrier density of ∼1 × 10 13 cm −2, comparable to the best values obtained on sapphire using Fe-doped GaN buffers. The best low temperature mobility of the 2-dimensional electron gas (2DEG) is ∼33, 000 cm 2 /V·s; indicating that the dominant scattering mechanism limiting the transport of 2DEG is interface roughness. Good quality BN grown directly onto sapphire is shown to be effective for reducing parallel conduction that exists due to residual donor impurities in the buffer. Luminescence measurements indicate good optical quality of the GaN/BN/sapphire. The residual strain in the GaN layer is found to be almost completely eliminated when it is released from the substrate.